Stabilized Earth Blocks: Innovative Materials in Modern Earthen Architecture - Amirreza adeghian; Roxana Abdollahi; Ali Akbari; Mehrdad Javidinejad (طراحی و برنامه ریزی در معماری و شهرسازی)
Earthen architecture, with its long history, still requires reflection and innovation in various areas such as technology, engineering, and laboratory testing. The current research focuses on stabilized earth blocks recognized as innovative materials in earthen architecture. Using technical specifications and laboratory tests, this study introduces them as a new approach to enhancing earthen architecture and its materials. The research methodology employed qualitative methods, relying on scientific and laboratory documents, along with library studies. These investigations demonstrate the considerable potential for development and improvement in earthen architecture, with stabilized earth blocks emerging as effective innovations in this field. Stabilized earth blocks, produced using the compressed earth block method, are considered among the most advanced products in earthen architecture. They utilize soil requiring technical processes like compression, stabilization, and various tests such as the jar test and compaction test. These blocks exhibit suitable flexibility and adhesive strength, enabling production in different dimensions for use in foundations, walls, beams, and ceilings of buildings. The advantages of these blocks include the advancement of earthen architecture both technically and practically, fostering new technology in the field. The importance of technical testing and production stages of these  roducts is emphasized in the article, highlighting their potential impact on the development and improvement of these innovative materials nationwide.